Sweet Deal, Bitter Landscape Gender Politics and Liminality in Tanzania's New Enclosures - Chung, Youjin (Cornell Series on Land: New Perspectives on Territory, Development, and Environment, 2024)
Sweet Deal, Bitter Landscape brings us to the mid-2000s, when the Tanzanian government struck a deal with a foreign investor to convert more than 20,000 hectares of long-settled coastal land to establish a sugarcane plantation. Ten years on, the deal was abruptly abandoned. Popularly deemed a case of hubristic global development, critics classified this project another in a line of failed modern resource grabs. Youjin B. Chung argues such tidy accounts conceal myriad and profound implications: not only how gender, history, and culture shaped the project's trajectory, but also how, even in its stalled state, the deal upended social life on the land by setting in motion incomplete processes of development and dispossession. With rich ethnographic detail and visual storytelling, Sweet Deal, Bitter Landscape traces the lived experiences of diverse rural women and men as they struggled for survival under a seemingly endless condition of liminality. In so doing, she raises critical questions about the directions and stakes of postcolonial development and nation-building in Tanzania, and the shifting meanings of identity and belonging for those on the margins of capitalist agrarian transformation.